Enhanced Phytoremediation Using Chelating Agents and Its Effects on Biomass Production and Metal Uptake by S. Jacquemontii (The Journal of Building and Land Development, 2025)
This study examined the potential of chelating agents, Ethylenediaminetetraacetic Acid and Citric Acid, to enhance phytoremediation of Pb, Cu, and Zn in contaminated soil using S. jacquemontii. A greenhouse pot experiment was conducted to evaluate the effects of EDTA and CA on biomass production and metal uptake. Soil contaminated with metals at concentrations of 300 mg/kg and 600 mg/kg were treated with chelates at the rate of 3 mmol/kg or 7 mmol/kg, while a control group received metals without chelating agents. Each treatment was triplicated to ensure reliability and accuracy in the results. Results demonstrated that both EDTA and CA significantly enhanced metal uptake (P